Effects of Different Pretreatment Methods on the Determination of Benzo (a) pyrene in Vegetable Oil - TAO Ru-qing; DU Li-juan (Liang you shipin ke-ji, 2023)
Three pretreatment methods, including direct extraction method, neutral alumina column method and molecular imprinted column method, were established for the determination of benzo (a) pyrene in vegetable oil by high performance liquid chromatography-fluorescence detector. The results showed that the linear relationship between the concentration of benzo (a) pyrene standard curve and the corresponding hromatographic peak area was good, and the correlation coefficient was 0.9993, when the concentration was in the range of 0.5~50 ng/mL. The blank vegetable oil was used as the matrix to carry out the spike recovery experiment. When the addition levels of benzo (a) pyrene were 2, 15 and 25 μg/kg, the average recoveries of direct extraction method, molecular imprinted column method and neutral alumina column method were 98.8%~102.8% and 91.1%~101.0% and 91.8%~113.7%, respectively, and the relative standard deviations (RSD) were 0.8%~2.0%, 2.3%~7.3% and 1.9%~8.8%, respectively. The direct extraction method has the advantages of simple pretreatment, good precision, high accuracy and sensitivity, and low cost, and is suitable for the detection of benzo (a) pyrene in vegetable oil.